Analisis Kemampuan Berpikir Kritis Siswa dalam Proses Belajar IPA Kelas IV Sekolah Dasar Melalui Media Pembelajaran Mini Turbin Pembangkit Listrik Tenaga Angin - Julianto; Suprayitno; Ineke Putri Wahyu Febriyanti; Nabila Putri; Kurniasari; Fitria Hidayati; Ekananda; Rahmadi; Salsabila (Postgraduate, University of Mataram, 2024)
Wind turbines work by converting wind into electrical energy. The moving turbine is exposed to the kinetic energy of the wind, while simultaneously driving a generator that can produce electricity. Wind electric energy is a simple, economical and non-polluting energy system. Several factors influence the performance of a wind turbine, such as wind speed, number of angles, and angle shape. The amount of wind power that can produce several coil (N) revolutions also affects the performance of the turbine. If the wind used is large, the pressure or movement made by the turbine will also be greater, so that the number of rotations produced will also increase, thus producing large amounts of electrical energy. The aim of this research is to help students think critically about natural science material. Carrying out this research is expected to be able to find out the character of students in learning, how students think about the material presented, and to find out how teachers provide natural science learning by involving learning media as a tool to help understand the material. The research method developed is Research and Development (RnD). The research model we use is to show how the media works to help explain electrical energy science material.